Using Cultivated Microbial Communities To Dissect Microbiome Assembly: Challenges, Limitations, and the Path Ahead - Benjamin E. Wolfe (American Society for Microbiology, 2018)
ABSTRACT As troves of microbiome sequencing data provide improved resolution of patterns of microbial diversity, new approaches are needed to understand what controls these patterns. Many microbial ecologists are using cultivated model microbial communities to address this challenge. These systems provide opportunities to identify drivers of microbiome assembly, but key challenges and limitations need to be carefully considered in their development, implementation, and interpretation. How well do model microbial communities mimic in vitro communities in terms of taxonomic diversity, trophic levels, intraspecific diversity, and the abiotic environment? What are the best ways to manipulate and measure inputs and outputs in model community experiments? In this perspective, I briefly address some of these challenges on the basis of our experience developing fermented food model communities. Future work integrating genetic and molecular approaches with cultivated model microbial communities will allow microbial ecology to develop a more mechanistic understanding of microbiome diversity.